1965
DOI: 10.1085/jgp.48.5.825
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Zinc on Contractility, Membrane Potentials, and Cation Content of Rat Atria

Abstract: Zinc depresses the contractile force of electrically driven rat atria logarithmically with time. The threshold concentration is about 5 X 10 -6 M zinc and the half-time for contractile depression at 10 -4 M is about 25 minutes. Zinc also depresses spontaneous activity of atria and alters the transmembrane potential parameters in a manner similar to quinidine. Unlike quinidine, zinc causes an elevation of the resting potential and an elevation of cellular potassium which varies with time in the same way as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

1970
1970
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…Coronary flow was unaltered. Negative inotropy and chronotropy have been reported by other investigators using isolated cardiac preparations exposed to 1 to 5000 pM zinc (302,303). In the study by Powell et al (301) zinc was also found to protect the heart during regional ischemia as indicated by a decrease in ventricular fibrillation during reperfusion and a decrease in release of lactic dehydrogenase.…”
Section: Health Effects Of Zinc Deficiency and Excess Effects On Orgamentioning
confidence: 71%
“…Coronary flow was unaltered. Negative inotropy and chronotropy have been reported by other investigators using isolated cardiac preparations exposed to 1 to 5000 pM zinc (302,303). In the study by Powell et al (301) zinc was also found to protect the heart during regional ischemia as indicated by a decrease in ventricular fibrillation during reperfusion and a decrease in release of lactic dehydrogenase.…”
Section: Health Effects Of Zinc Deficiency and Excess Effects On Orgamentioning
confidence: 71%
“…Ciofalo and Thomas (7). Neither group could demonstrate that the graded negative contractile responses following perfusion of cardiac tissue with Zn were attributable to impaired cellular electrical activity.…”
Section: Discussionmentioning
confidence: 93%
“…There is cross-talk between the fluxes of Ca 2+ and Zn 2+ [106]; hence, it is thought that zinc dyshomeostasis will impact on Ca 2+ trafficking in cardiomyocytes (as recently reviewed in [107]). Various studies suggest that defective Zn 2+ handling contributes to cardiomyopathies including altered contractility and heart failure [89,[108][109][110]. Indeed, it has been hypothesised that increased cytosolic Zn 2+ can influence cardiac excitationcontraction coupling through regulation of the ryanodine receptor in cardiomyocytes [111,112].…”
Section: +mentioning
confidence: 99%